(untitled) (The Review of Diabetic Studies, 2024)
Background Medical secretaries and healthcare assistants (HCAs) play a foundational role in the functioning of healthcare organizations by managing administrative duties that ensure smooth communication and coordination between patients, clinicians, and healthcare departments. Regarding professional identity, patient acceptance, cost-effectiveness, patient safety and delegation, training and competence, and workforce development are prompted by the introduction of healthcare assistants (HCAs) into general practice. However, the rapid evolution of healthcare systems driven by technological advancements, regulatory changes, and growing patient-centered care models—has significantly altered the scope of the medical secretary’s role and healthcare assistants .The integration of medical secretaries, healthcare assistants (HCAs) plays a pivotal role in enhancing Modern Healthcare Systems high-quality patient care, minimizing operational costs, and reducing healthcare staff burnout. Aim of this systematically review: To explores the multifaceted responsibilities of medical secretaries and healthcare assistants (HCAs) with a particular focus on their crucial role in Modern Healthcare Systems in Saudi Arabia2024. Method: The study employs a systematic review approach to synthesize the literature on role of the Medical Secretary and health assistant in Modern Healthcare Systems, drawing insights from a wide range of sources including research articles, reports, and news articles. Results: healthcare quality improvement initiatives has increased the emphasis on reducing administrative burdens on clinical staff. As a result, the role of the medical secretary and health assistant has expanded from a passive clerical function to a dynamic, multifaceted support position that contributes directly to operational efficiency, patient safety, and overall service quality. Despite this transformation, limited academic attention has been devoted to examining the evolving role of the medical secretary and health assistant in Saudi Arabia. Conclusion: Medical secretaries and health assistant play a vital role in promoting inter professional collaboration and effective team dynamics in healthcare settings. Optimizing their role through clear job descriptions, training and recognition can enhance teamwork and ultimately improve patient care, modern Healthcare Systems. Further research is needed to develop and evaluate interventions to support the integration of medical secretaries and health assistant in healthcare teams.